Penerapan Metode Scramble untuk Meningkatkan Minat Belajar Siswa pada Mata Pelajaran PAI Kelas IX SMP Negeri 2 Peterongan Jombang - Mustafidah, Livia; Chotimah, Chusnul (Lembaga Yasin AlSys, 2025)
This study aims to analyze the application of the scramble method in enhancing students' learning interest in Islamic Education (PAI) subjects for grade IX at SMP Negeri 2 Peterongan, Jombang. Learning interest is a crucial factor in the success of the learning process, and the scramble method was chosen due to its interactive, engaging approach that enhances student engagement. This final project employs qualitative research methods. Qualitative research is a type of inquiry that generates analysis without involving statistical procedures or other forms of quantification. The data collected in this study include field notes, observation, interview, documentation, rather than numerical data. Therefore, the approach used in this research is a qualitative, naturalistic approach that aims to understand and explore the meaning of a phenomenon within a specific environmental context. The study utilizes a qualitative approach with data collection techniques such as observation, interviews, and documentation. The findings show that the scramble method is effective in increasing students' learning interest. Students became more enthusiastic, understood the material more easily, and exhibited better critical thinking skills. Supporting factors for implementing this method include its flexibility, student collaboration, and improved conceptual understanding. However, some challenges were identified, such as the need for thorough preparation, complex classroom management, and varying student abilities. In conclusion, the scramble method is an effective learning strategy to enhance students' interest in PAI material, particularly on the topic of Hajj. This method creates a fun and interactive learning environment, though it requires intensive preparation from teachers.